Modeling the resilient supply of ecosystem function for climate change adaptive management in Wetland City. (15th November 2022) - Jin, Lilan; Kim, Min; Chon, Jinhyung
Abstract: Rapid urbanization causes wetland ecosystem functions to degrade worldwide. This phenomenon negatively affects the resilience of ecosystem functions in the face of unexpected impacts, particularly climate change. An approach is required for combining resilience with management in a Wetland City. This study aims to model the resilience of ecosystem functions for climate change adaptation management in a Wetland City via system dynamics from 2021 to 2100. First, we set a system boundary through expert interviews to identify the main issues in the social-ecological system of a Wetland City. Second, we constructed a social-ecological system of a Wetland City that provides ecosystem function trade-offs between flood control and wildlife habitat provisioning. Then, we simulated the resilience of ecosystem functions according to different climate change adaptative management scenarios. Finally, we determined an appropriate scenario for minimizing the impacts of ecosystem function trade-offs reinforced by climate change. As a result, we recommend that the water level should be managed such that the controlled flood water level ranges from 12 to 14 m and that 30% of the willow areas should be thinned each year. Based on these simulation results, we proposed three climate change adaptive management strategies: considering long-term plans including short-term effects, networking with multiscale community participation, and applying sustainable wetland management to urban planning. Ultimately, this study can contribute to planning and management guidelines for a Wetland City. Highlights: The Upo Wetland has ecosystem function trade-offs between flood control and wildlife habitat provisioning. We simulated various climate change adaptive strategies to enhance the desired ecosystem functions over time. Willow thinning and water level control could balance the resilience of Upo Wetland's ecosystem function. Three adaptive management strategies can be used to guide a Wetland City.